Implementation The Policy of Prevention and Stunting Management (Study of Regional Regulation Number 7 of 2021 Concerning Prevention and Stunting Management in South Bangka) - Isneni Neka Indriyani; Ibrahim; Sarpin (Social Science Studies, 2022)
The study in this research discusses the implementation of the policy of prevention and stunting management in South Bangka. Stunting cases in South Bangka from 2020 to 2021 experienced the additional of stunting locus. If in 2020 stunting cases were found in 8 villages, in 2021 the number of stunting locus increased to 14 villages. The purpose of this study is to determine the implementation of the policy of prevention and stunting management in South Bangka, along with obstacles faced in implementing the policy. The theory used in this research is the theory of Van Meter and Van Horn (1975). In addition, qualitative research method with descriptive data analysis is used in this study. The results of this study conclude that the implementation of the policy of prevention and stunting management in South Bangka has been running quite well and the planned programs/activities are able to carry out well, although the policy made has only been running for one and a half years, it succeeded in reducing the stunting prevalence rate from 7.7% to 3.62%. During the implementation of the policy, it is obvious that there are certain obstacles. These obstacles, among others, relate to the COVID-19 pandemic, which makes the stunting management programs/activities realizations limited. Furthermore, there is the problem of understanding from parents regarding stunting along with an unhealthy lifestyle. Moreover, there is a lack of funding, lack of coordination between policy implementers, and limited human resources.